QM Computations on Complete Nucleic Acids Building Blocks: Analysis of the Sarcin-Ricin RNA Motif Using DFT-D3, HF-3c, PM6-D3H, and MM Approaches - Kruse, Holger; Havrila, Marek; Šponer, Jiřı (Journal of chemical theory and computation, 2014)
A set of conformations obtained from explicit solvent molecular dynamics (MD) simulations of the Sarcin-Ricin internal loop (SRL) RNA motif is investigated using quantum mechanical (QM, TPSS-D3/def2-TZVP DFT-D3) and molecular mechanics (MM, AMBER parm99bsc0+χol3 force field) methods. Solvent effects are approximated using implicit solvent methods (COSMO for DFT-D3; GB and PB for MM). Large-scale DFT-D3 optimizations of the full 11-nucleotide motif are compared to MM results and reveal a higher flexibility of DFT-D3 over the MM in the optimization procedure. Conformational energies of the SRL motif expose significant differences in the DFT-D3 and MM energy descriptions that explain difficulties in MD simulations of the SRL motif. The TPSS-D3 data are in excellent agreement with results obtained by the hybrid functionals PW6B95-D3 and M06-2X. Computationally more efficient methods such as PM6-D3H and HF-3c show promising but partly inconsistent results. It is demonstrated that large-scale DFT-D3 computations on complete nucleic acids building blocks are a viable tool to complement the picture obtained from MD simulations and can be used as benchmarks for faster computational methods. Methodological challenges of large-scale QM computations on nucleic acids such as missing solvent-solute interactions and the truncation of the studied systems are discussed.